The Principle of Justice Based on Pancasila in the Application of the Dismissal Process in Indonesian Civil Procedure Law - Febrian Rizki Pratama; Asrul Imam; Nizar Ali (Faculty of Law, University of Dr. Soetomo, 2026)
This article examines the principle of justice based on Pancasila as the philosophical foundation for the application of the dismissal process in Indonesian civil procedure law. The research method employed is normative legal research. The discussion traces the development of the concept of justice from various schools of Western, Eastern, and Islamic philosophy, as well as Indonesian legal thought, culminating in Pancasila-based justice as the national legal ideal. In civil procedure law, the dismissal process is understood as an initial mechanism to maintain a balance between access to justice for plaintiffs and the protection of defendants’ rights from lawsuits that do not meet legal requirements. Its application must reflect humanistic values, equality before the law, and social justice, so that the dismissal process functions not only as an instrument of judicial efficiency but also as a means of realizing Pancasila justice.